CLINICAL MANIFESTATION OF SIMPLE AND PROLIFERATING TYPE OF UTERINE FIBROIDS - Alibekov Omadbek Ozodbekovich (Scholar Express Journals, 2024)
The study noted a high incidence of somatic and gynecological diseases in patients with uterine myoma. It was noted that menstrual dysfunction, hyperpolymenorrhea and menorrhagia, primary infertility is higher in proliferative fibroids than in patients with simple fibroids
Keywords: simple myoma; proliferative myoma; infertility; hyperpolymenorrhea